Implementation of Sharia Economic Law in Modern Business Transactions in Indonesia - Muhammad Rasyid Ridoh; Rajindra, Rajindra (Universitas Muhammadiyah Palu, 2025)
This study examines the implementation of Sharia Economic Law in modern business transactions in Indonesia, focusing on how Islamic legal principles are applied within contemporary economic activities. As Indonesia continues to experience rapid digital and financial innovation, various sectors—including banking, e-commerce, fintech, and Islamic microfinance—have increasingly adopted Sharia-compliant mechanisms. This research analyzes the extent to which Sharia principles such as fairness, transparency, avoidance of usury (riba), uncertainty (gharar), and prohibited transactions (maysir) are integrated into current business practices. Using a qualitative approach through literature review, regulatory analysis, and case studies from selected Sharia-based financial institutions, the findings reveal that Sharia Economic Law plays a significant role in shaping ethical business conduct and providing legal certainty in modern transactions. However, several challenges remain, including regulatory harmonization, public literacy, and the need for stronger supervision frameworks. Overall, this study highlights the importance of strengthening Sharia-compliant systems to support sustainable and equitable economic development in Indonesia.